TEATR HÁM KÓRKEM ÓNER (ART AND CULTURE BULLETIN, 2023)
Numerous performances are acted on the stage, performed by folk music, and musicperformed by orchestras, from the kind of people. Theater and music occupy the same place in the art. Forthis reason, it can be mentioned that Karakalpak theatres are currently developing.
Keywords: music; drama; opera; ballet; puppet theater; pantomime.